2015
DOI: 10.1088/0953-8984/27/44/445502
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of confined gallium clusters

Abstract: We report the results of ab initio molecular dynamics simulations of Ga13 and Ga17 clusters confined inside carbon nanotubes with different diameters. The cluster-tube interaction is simulated by the Lennard-Jones (LJ) potential. We discuss the geometries, the nature of the bonding and the thermodynamics under confinement. The geometries as well as the isomer spectra of both the clusters are significantly affected. The degree of confinement decides the dimensionality of the clusters. We observe that a number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…This can be correlated to a pronounced confinement effect on the NP structure. Indeed, the morphologies of cluster/NP under confinement turn out to be very different as compared to the free or supported cluster/NP (see Figure for the case of Pt). , It has been clearly demonstrated that these structural changes of confined species have a direct impact on the properties of the NP.…”
Section: Why Anchoring Metal Nanoparticles Clusters or Metal Single A...mentioning
confidence: 98%
“…This can be correlated to a pronounced confinement effect on the NP structure. Indeed, the morphologies of cluster/NP under confinement turn out to be very different as compared to the free or supported cluster/NP (see Figure for the case of Pt). , It has been clearly demonstrated that these structural changes of confined species have a direct impact on the properties of the NP.…”
Section: Why Anchoring Metal Nanoparticles Clusters or Metal Single A...mentioning
confidence: 98%
“…Considering the fact that the adjacent layers in GaTe nanosheets, the indenter tip and the uppermost GaTe layer, the SiO 2 substrate and the lowermost GaTe layer were all interacted through the long-range vdW force, the Lennard-Jones (LJ) 12-6 potential was utilised to describe these vdW interactions. Here, the LJ parameters were taken from [55][56][57] for GaTe-GaTe, GaTe-C and GaTe-SiO 2 interactions, respectively. The values of these LJ parameters are listed in the supplementary materials (table S1).…”
Section: Simulations Of the Freestanding Indentation Of Gate Nanosheetsmentioning
confidence: 99%